Women, Gender, and Feminist Studies (International Journal of Scientific Research in Science and Technology, 2025)
Women studies is different frrom gender studies Women studies is interdisciplinary subjectand it is very important for in academics for understandingicproblem.In 1893 New Zealand was the first country who give right to vote for women. After that in 1910’s several countries like USA,Russia and Germany gave right to vote forWomen. India gave right to vote at the very beginning of the making of the constitution. We have very big problem of adverse child sex ratio and anaemia along with undernourished children National family Health survey is the main source of data regarding health of women Child wasting and child stunting is also the main problems in India It is fourtunate that we are going to achieve Total fertility rate 2.1 target. TFR 2.1 is the replacement level of population. that is our population will stabilize and than stationary population we will haveIt means the population growth rate will be zero in future .Women studies is very dynamic subject Because this subject is more objective rather than subjective. Case studies are very important for deeper learning.